Caregiver burden among Chinese family caregivers of patients with lung cancer: A cross-sectional survey. (December 2018) - Hu, Xiaolin; Peng, Xingchen; Su, Yonglin; Huang, Wenxia
Abstract: Purpose: To investigate the status of caregiver burden and to identify the factors related to caregiver burden among Chinese family caregivers of patients with lung cancer. Methods: A cross-sectional design with convenience sampling was used in this study. Participants (N = 116) from the oncology inpatient ward at one teaching hospital in Chengdu were recruited from June 2015 to June 2016. The following measurement tools were used: a demographic questionnaire, the Social Support Rating Scale, the General Self-efficacy Scale, and the Zarit Burden Interview. Multiple linear regression analysis was used to identify factors associated with caregiver burden. Results: The average ZBI score was 38.8 (SD = 13.4). Patient age (p < 0.01), medical and other types of insurance (p < 0.01), disclosure of the diagnosis to patients (p < 0.01), and social support of the caregiver (p < 0.05) were related to caregiver burden. Fifty-three percent of the variance in caregivers' burden was explained by these identified factors. Conclusions: Caregiver burden was higher among Chinese caregivers of lung cancer patients compared with the results of previous studies. Patient age, medical and other types of insurance, disclosure of cancer diagnosis to the patient, and caregivers' social support are factors associated with caregiver burden. The results suggest that social support, comprehensive healthcare insurance initiatives, and culture-based communication skill training are potential areas for future intervention. Highlights: Patient age, disclosure of the diagnosis to the patient, payment type, and caregivers' social support are factors related to caregiver burden. A well-designed communication skills training programme with the integration of Chinese customs is recommended. Family caregivers may benefit from healthcare insurance initiatives, a communication training programme, and social and economic support.